The Land Use - Land Degradation Nexus in Mediterranean Landscapes: – Drivers of Changes And Key Processes at Selected Natura 2000 Sites of Crete, Greece - Meyer, Burghard C.; Kirsten, Fabian; Sattler, Dietmar; Heinrich, Jürgen (Journal of Environmental Geography, 2020)
The land use–land degradation nexus in Cretan landscapes in regions with Natura 2000 sites was analyzed by an explorative expert driven study based on literature, field work and photo documentation methods with the aim of determining status, drivers and key processes of change. Drivers of current land use changes have been worked out by (1) general tourism developments and tourism related land uses; (2) irrigated olive yard developments; (3) fenced large-scale goat pastures and (4) large scale greenhouses. Key processes of change have been identified and qualitatively assessed for 5 regions with NATURA 2000 areas based on a non-ranked set of 11 descriptive indicators. The analysis includes the status-description and the importance assessment of land degradation processes in selected NATURA 2000 sites. Threats and pressures taken from the NATURA 2000 documentation and the land use – land degradation nexus and the analysis are a suitable basis for future land management in order to reach land degradation neutrality. The result of our analysis opens a new research field for a better integration of the normally thematically isolated analysis in geography, biology/nature conservation and agricultural policy analysis about the drivers and processes in landscape systems towards a better understanding the trends in land cover change (e.g. vegetation/soil degradation), the trends in productivity or functioning changes caused by land uses and as well for the trends in carbon stock change.